TRANSPARANSI DAN AKUNTABILITAS PEMERINTAH DAERAH DALAM RELOKASI PEDAGANG: STUDI KASUS PASAR RAU KOTA SERANG - Zahra, Siti; Putri, Harlida Aliya; Rizki, Alinda Nur (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2025)
This study examines how local governments implement transparency and accountability during the relocation of traders at Rau Market, Serang City. This policy has an impact on spatial planning and development infrastructure as well as the economic sustainability of small traders. This study uses a qualitative descriptive approach based on secondary data, namely official documents, media reports, and public information archives. The study found that information about the relocation was not communicated evenly and did not fully address the vendors' needs regarding kiosk allocation, costs, facilities, and projections of economic conditions after relocation. This raised concerns and perceptions that the policy was implemented unilaterally. Due to the government's tendency toward one-way communication, vendor participation in the decision-making process was also limited. From an accountability perspective, the government assesses the success of relocation through the completion of physical construction, while traders assess success through income stability and the number of customers after relocation. This shows that there are differences in evaluation that have not been fully addressed. Overall, this study shows that market relocation can only be accepted and implemented if the government applies information transparency, opens space for substantial discussion, and provides responsive accountability mechanisms. Thus, relocation not only results in physical changes but also supports the economic sustainability of traders and increases public trust.